Refeeding and metabolic syndromes: two sides of the same coin - Obeid, O A (Nature Publishing Group, 2014)
Refeeding syndrome describes the metabolic and clinical changes attributed to aggressive rehabilitation of malnourished subjects. The metabolic changes of refeeding are related to hypophosphatemia, hypokalemia, hypomagnesemia, sodium retention and hyperglycemia, and these are believed to be mainly the result of increased insulin secretion following high carbohydrate intake. In the past few decades, increased consumption of processed food (refined cereals, oils, sugar and sweeteners, and so on) lowered the intake of several macrominerals (mainly phosphorus, potassium and magnesium). This seems to have compromised the postprandial status of these macrominerals, in a manner that mimics low grade refeeding syndrome status. At the pathophysiological level, this condition favored the development of the different components of the metabolic syndrome. Thus, it is reasonable to postulate that metabolic syndrome is the result of long term exposure to a mild refeeding syndrome.